A review of pseudorabies (aujeszky's disease) in pigs - Lee, J. Y. S; Wilson, M. R. (Canadian Veterinary Medical Association, 1979)
The main features in terms of etiology, clinical signs, pathogenesis, pathology, diagnosis, epizootiology and control and prevention that are known about pseudorabies are briefly reviewed. Areas still lacking in information which may provide more effective and reliable means of dealing with pseudorabies are mentioned and recommendations using available tools and knowledge to deal with the problem of pseudorabies are given.